Right versus left ventricular remodeling in heart failure due to chronic volume overload - Havlenova, Tereza; Skaroupkova, Petra; Miklovic, Matus; Behounek, Matej; Chmel, Martin; Jarkovska, Dagmar; Sviglerova, Jitka; Stengl, Milan; Kolar, Michal; Novotny, Jiri; Benes, Jan; Cervenka, Ludek; et al. (Scientific reports, 2021)
Mechanisms of right ventricular (RV) dysfunction in heart failure (HF) are poorly understood. RV response to volume overload (VO), a common contributing factor to HF, is rarely studied. The goal was to identify interventricular differences in response to chronic VO. Rats underwent aorto-caval fistula (ACF)/sham operation to induce VO. After 24 weeks, RV and left ventricular (LV) functions, gene expression and proteomics were studied. ACF led to biventricular dilatation, systolic dysfunction and hypertrophy affecting relatively more RV. Increased RV afterload contributed to larger RV stroke work increment compared to LV. Both ACF ventricles displayed upregulation of genes of myocardial stress and metabolism. Most proteins reacted to VO in a similar direction in both ventricles, yet the expression changes were more pronounced in RV (pslope: < 0.001). The most upregulated were extracellular matrix (POSTN, NRAP, TGM2, CKAP4), cell adhesion (NCAM, NRAP, XIRP2) and cytoskeletal proteins (FHL1, CSRP3) and enzymes of carbohydrate (PKM) or norepinephrine (MAOA) metabolism. Downregulated were MYH6 and FAO enzymes. Therefore, when exposed to identical VO, both ventricles display similar upregulation of stress and metabolic markers. Relatively larger response of ACF RV compared to the LV may be caused by concomitant pulmonary hypertension. No evidence supports RV chamber-specific regulation of protein expression in response to VO.
Keywords: Pyruvate Kinase; Stroke Volume; srdeční komory; Extracellular Matrix Proteins; Cell Adhesion Molecules; Male; srdeční selhání; potkani Sprague-Dawley; proteom; protein-glutamin:amin-gama-glutamyltransferasa 2; molekuly buněčné adheze; Myocardium; mužské pohlaví; tepový objem; Ventricular Remodeling; krysa rodu Rattus; Protein Glutamine gamma Glutamyltransferase 2; extracelulární matrix - proteiny; Animals; Heart Failure; pyruvátkinasa; zvířata; Rats; Heart Ventricles; Proteome; remodelace komor; myokard; Rats, Sprague-Dawley